Analysis of food irradiation education for elementary, middle, and high school students for three years in South Korea - Choi, Yoonseok (Nutr Res Pract, 2016)
BACKGROUND/OBJECTIVES: The current South Korean government policy on food irradiation technology should be reformed based on an in-depth investigation of the communications aspect, because the issue is no longer of a technological nature, given the proven safety and efficacy of the processes. SUBJECTS/METHODS: The target population of the education program consisted of elementary, middle, and high school students attending 310 schools in South Korea (2013: 63 schools, 2014: 104 schools, 2015: 143 schools). Data subjected to analysis were 13,327 pre-education and 12,641 post-education questionnaires received from 7,582 elementary, 2,671 middle, and 3,249 high school students who participated in the education program from May 2012 to April 2015 (n = 12,831), after the exclusion of inadequately filled-in questionnaires. RESULTS: Analysis of the three-year educational effect trend was conducted by comparing levels of variables before and after food radiation education. The analysis yielded the finding that the post-education levels were significantly higher for all variables. That is, for interest in education, perception (necessity, safety, subjective knowledge, and information acquisition), objective knowledge, and attitude, with the sole exception of objective knowledge in 2013. CONCLUSIONS: Given that post-education levels of perception, knowledge, and attitude concerning irradiated foods increased considerably compared to pre-education levels, behavior change should be induced by providing continuous education to enhance, these primary variables.